PROCESSES OF BLEACHING AND DISCOLOURING OF WOOL FIBERS - O.A.Toshbekov; M.K.Urozov; N.R. Baymurova; M.F. Hamrayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The main part of local wool fibers grown in the country is coarse and semi-coarse. It is advisable to produce high-quality yarn, textiles and non-woven products from wool from local sheep, goats and camels. At the same time, improving the surface appearance of products will lead to an increase in demand, the technology of bleaching, discoloring of wool fiber on the basis of local raw materials has been developed and the technology of production of non-woven fabrics of different thicknesses has been expanded.